G25(P) Neonatal emergency simulation training (NEST) in a district general hospital – delivery and outcomes. (24th May 2017) - Lawton, L; Workman, H; Verma, N; Thakur, I; Garbash, M
Abstract : Purpose: Across the UK, special care baby units experience a lower frequency of critical/emergency clinical situations than higher level units, and as a result, maintaining standards and enhancing performance is a challenge. We have supplemented our clinical experiences with hi-fidelity simulation scenarios relevant to the general paediatric and neonatal nursing teams working in our special care units. We have ascertained the effectiveness of this pilot programme prior to further implementation. Methods: Our Trust has 2 acute sites across which there are over 5000 deliveries annually. In order to successfully support this initiative we have trained 13 faculty – 4 medical and 9 neonatal nurses – and have invested in both a high fidelity term manikin and lower fidelity preterm manikin. Sessions take place within the normal working environment, providing better immersion and an opportunity to test real-life systems, while working within the multi-disciplinary team. Each scenario is designed to examine clinical skills, decision making, leadership, team-working and communication skills. Debriefs are facilitated by a faculty member, but the learning and reflection come from the participants themselves, which we believe is much more powerful. Results: We used a likert scale, covering 7 domains, when requesting feedback. All scores are mean scores out of 5. (5 being excellent and 0 being inadequate) Conclusion: Despite the challenges we have faced, these results affirm that this initiative is of benefit to both clinicians and nurses in the special care setting, helping to improve team-working, decision making and communication in challenging circumstances. Improvements and modifications can be made, particularly around the recognition and management of the sick neonate. However, given this positive feedback we are encouraged to continue to implement this programme. We expect that these sessions will enhance performance and maintain skills in critical/ emergency neonatal clinical situations, and above all ensure that we provide the best care for babies born in hospitals with special care level services.